Towards a mechanism-based approach to pain management in osteoarthritis - Malfait, Anne-Marie (2013)
Pain is the defining symptom of osteoarthritis (OA), yet available treatment options, of which NSAIDs are the most common, provide inadequate pain relief and are associated with serious health risks when used long term. Chronic pain pathways are subject to complex levels of control and modulation, both in the periphery and in the central nervous system. Ongoing clinical and basic research is uncovering how these pathways operate in OA. Indeed, clinical investigation into the types of pain associated with progressive OA, the presence of central sensitization, the correlation with structural changes in the joint, and the efficacy of novel analgesics affords new insights into the pathophysiology of OA pain. Moreover, studies in disease-specific animal models enable the unravelling of the cellular and molecular pathways involved. We expect that increased understanding of the mechanisms by which chronic OA-associated pain is generated and maintained will offer opportunities for targeting and improving the safety of analgesia. In addition, using clinical and genetic approaches, it might become possible to identify subsets of patients with pain of different pathophysiology, thus enabling a tailored approach to pain management.